Estudio sobre la aproximación a la cultura planteada por Bolívar Echeverría - Bryan Alexander, Méndez Tarupi (2021)
ABSTRACT Based on the work of Bolívar Echevería about culture, this investigative work establishes a relationship of the different topics published in his works around culture, thus establishing an approach to the thinking of the philosopher Bolívar Echeverrìa, developing an analysis that has fidelity to its cultural, ideological current. First, the most important postulates of his works are outlined by points to obtain the analysis of his contributions, references to the concept of culture, as well as the origin of the Ecuadorian philosopher's thought, which are his intellectual origins and how they are found through the time. The second point is related to the cultural concepts of the thinker: from the Ethos and the Baroque, going through the cultural factors that appear in civilization, the importance of the study of the cultural and the criticism of modern capitalism without leaving aside the study of the production of culture through the postulates of Marx; the sign, language, and its production as the central axis basic communication needs. In this work, the author reviews temporality and cotidianity to explain how culture appears in the newspaper, in the language, as it is distributed in the game, in art, and the party. Keywords: Bolívar Echeverría, Culture, Production. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR cc: 1002091161